STRUCTURALLY FUNCTIONAL CHARACTERISTICS OF IDENTITY WITH DIFFERENT LEVEL OF SELF-EFFICIENCY - Anartasiya Sergeevna Shershneva (Вестник Северо-Кавказского федерального университета)
Features of structure of identity and functional characteristics of properties of the subject of communicative and professional activity depending on level of self-efficiency of the personality are analyzed